Pollution Control Strategy to Prevent the Degradation of River Water Quality (Case Study of Talawaan River, Minahasa Regency, North Sulawesi Province) - Fadillah Putra; Alfa Winny Pongoh; Soemarno Soemarno (Postgraduate School Universitas Brawijaya, 2021)
This research was conducted to analyze and describe the Pollution Control Strategy for Preventing Degradation in the Water Quality of the Talawaan River in Minahasa Regency, North Sulawesi Province. This research used the descriptive-quantitative method. This research was carried out in the Talawaan River, North Minahasa Regency. The data were analyzed using SWOT analysis and an analytical hierarchy process. The results showed that the increase in water quality as a control over the contamination of the Talawaan River with a diversification strategy (Strength - Threats strategy) has the highest total weight in the effort to compile a complete information system to support water pollution control policies. Thus, the alternative strategic priority is to develop a complete information system to support water pollution control policies and then invite community participation in controlling river water pollution and controlling waste that enters the river. Keywords: control, pollution, water quality, talawaan river